BUSINESS BEHAVIOR OF TARIQA FOLLOWERS IN INDONESIA: The Relation of Religion, Sufism, and Work Ethic - Djakfar, Muhammad (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2018)
In Islam, people know a teaching and mystical practice called sufism. Its main objective is to purify oneself (tazkiyat al-nafs) to get closer to God. Time-wise, sufism can be mapped into orthodox and neo-sufism. Teaching substance-wise, it is classified into akhlâqî and falsafî sufism. So far, commoners and academician such as Max Weber believe that sufism followers behave asceticly, live an austere life, have no capitalistic spirit, and so forth. This false perception obviously needs a correction for people understand the behavior of tariqa followers as an organized sufism community among society. In Indonesia, tariqa followers include Sadziliyah and Shiddiqiyah. The basic question is if they live an austere life so they do not have to contribute to the economic life of nation. Result study shows that according to Sadziliyah people, wealth has spiritual, economic, and social meaning by centralizing business activities in houses and market. Meanwhile, Shiddiqiyah followers consider that wealth has spiritual, economic, social, cultural, and preached meaning in various efforts. Therefore, both tariqas teach a balance between spiritual (worship) and material obligations, ukhrâwiyah and dunyâwiyah obligations as taught by neo-sufism. In addition, it shows a relationship among religion, sufism, and work ethic.